Préoccupations et résultats scientifiques roumaines concernant la lutte contre la pollution des eaux avec des produits pétroliers - Șerbănescu, Octavian (Cercetări Marine - Recherches Marines, 2026)
The author presents the main achievements of the Romanian Marine Research Institute - Constanta, concerning the oil pollution control in marine and freshwater environments. The means used and general technology of intervention in oil pollution control are described in the paper.